2016
DOI: 10.1103/physrevphyseducres.12.020124
|View full text |Cite
|
Sign up to set email alerts
|

Beyond performance metrics: Examining a decrease in students’ physics self-efficacy through a social networks lens

Abstract: The Modeling Instruction (MI) approach to introductory physics manifests significant increases in student conceptual understanding and attitudes toward physics. In light of these findings, we investigated changes in student self-efficacy while considering the construct's contribution to the career-decision making process. Students in the Fall 2014 and 2015 MI courses at Florida International University exhibited a decrease on each of the sources of self-efficacy and overall self-efficacy (N ¼ 147) as measured … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 46 publications
(90 reference statements)
1
69
0
8
Order By: Relevance
“…The most common method for addressing missing data in PER is to use listwise deletion to only analyze the complete cases, discarding data from any student who did not provide both the pretest and post-test; though, we know of at least one study in PER that used MI [32]. We used MI because it has the same basic assumptions of listwise deletion but it reduces the rate of type I error by using all the available information to better account for missing data [33].…”
Section: A Data Collection and Processingmentioning
confidence: 99%
“…The most common method for addressing missing data in PER is to use listwise deletion to only analyze the complete cases, discarding data from any student who did not provide both the pretest and post-test; though, we know of at least one study in PER that used MI [32]. We used MI because it has the same basic assumptions of listwise deletion but it reduces the rate of type I error by using all the available information to better account for missing data [33].…”
Section: A Data Collection and Processingmentioning
confidence: 99%
“…For over half a decade we have applied SNA in the field of physics education research. That work has led to greater understandings of student persistence, changes in their career-related beliefs (e.g., physics interest), and their academic success [7,8,[12][13][14]. In the process, we also established SNA study design in the classroom arXiv:1809.00337v1 [physics.ed-ph] 2 Sep 2018 context, including development of data collection instruments, setup of protocols for gathering and digitizing data, as well as identification of network methodologies relevant to a wide range of research questions.…”
Section: Introductionmentioning
confidence: 99%
“…Learning is perceived as a construction of mutual understandings within a social context, with emphasis placed on examining discourse and interactions rather than "acquisition" of knowledge as a commodity or object [17]. As such, we espouse the philosophy that "learning and social interactions are not mutually exclusive" [12].…”
Section: Anxiety In the Introductory Physics Classroommentioning
confidence: 99%
“…In addition, several studies have used SNA to quantify interactions in order to explore their impact on other constructs relevant to learning (e.g., course grades [7], self-efficacy [8], persistence [9]). …”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%
“…In most of these studies [5,[7][8][9], ties were identified using self-reported data from a survey where participants name individuals with whom they interact. We propose an application of SNA where ties are instead extracted from qualitative analysis of classroom video data.…”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%